Bernstein-Type Theorems and Uniqueness Theorems - Logvinenko, V.; Nazarova, N. (Український математичний журнал, 2004)
Let f be an entire function of finite type with respect to finite order ρ in Cⁿ and let E be a subset of an open cone in a certain n-dimensional subspace R²ⁿ ( = Cⁿ) (the smaller ρ , the sparser E ). We assume that this cone contains a ray {z = tz⁰ ∈ Cn: t > 0} . It is shown that the radial indicator hf(z⁰) of f at any point z⁰ ∈ Cⁿ∖{0} may be evaluated in terms of function values at points of the discrete subset E . Moreover, if f tends to zero fast enough as z→∞ over E , then this function vanishes identically. To prove these results, a special approximation technique is developed. In the last part of the paper, it is proved that, under certain conditions on ρ and E , which are close to exact conditions, the function f bounded on E is bounded on the ray Нехай f — ціла функція скінченного типу відносно порядку ρ у Cⁿ, E — підмножииа відкритого конуса (чим менше ρ , тим більш розрідженим є E у деякому n-вимірному підпросторі R²ⁿ ( = Cⁿ). Припускається, що даний конус містить промінь {z = tz⁰ ∈ Cⁿ: t > 0}. Показано, що радіальний індикатор hf(z⁰) функції f у будь-якій точці z⁰ ∈ Cⁿ∖{0} можна оцінити через значення функції f у точках дискретної множини E. Крім того, якщо f→0 досить швидко при z→∞ на E, то дана функція дорівнює нулю тотожно. Для доведення цих результатів розроблено спеціальну апроксимаційну техніку. В останній частині роботи доведено, що за деяких близьких до точних умов відносно ρ і E функція /, обмежена на E, буде обмеженою па всьому промені.